2019
DOI: 10.1039/c8bm01221k
|View full text |Cite
|
Sign up to set email alerts
|

Versatile iron–catechol-based nanoscale coordination polymers with antiretroviral ligand functionalization and their use as efficient carriers in HIV/AIDS therapy

Abstract: Iron-based nanoscale coordination polymers as novel drug delivery systems for efficient HIV/AIDS therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…These polymers offered long-lasting drug release and improved colloidal stabilities, as well as enhanced cellular uptake (ie, an increase of up to 50fold). 144 The proliposomes increased the MRT of adefovir dipivoxil in the liver by approximately 3-fold compared with the adefovir suspension. 145 The poly (lactic acid)-poly (ethylene glycol)-ligand NPs targeted the intestinal transporter PepT1 and increased permeability by 2.7-fold compared with free acyclovir.…”
Section: Nanotechnology To Improve Pharmacokinetics Of Avds Delivery System To Improve Pharmacokineticsmentioning
confidence: 95%
“…These polymers offered long-lasting drug release and improved colloidal stabilities, as well as enhanced cellular uptake (ie, an increase of up to 50fold). 144 The proliposomes increased the MRT of adefovir dipivoxil in the liver by approximately 3-fold compared with the adefovir suspension. 145 The poly (lactic acid)-poly (ethylene glycol)-ligand NPs targeted the intestinal transporter PepT1 and increased permeability by 2.7-fold compared with free acyclovir.…”
Section: Nanotechnology To Improve Pharmacokinetics Of Avds Delivery System To Improve Pharmacokineticsmentioning
confidence: 95%
“…In particular, catechol–Fe(III)–catechol crosslinking led to self‐healing hydrogels 108. Subsequently, numerous hydrogels using catechol/Fe(III) binding109 as well as force measurements of bis‐catechol‐Fe 3+ (200 pN) and tris‐catechol‐Fe 3+ (100 pN) at the single molecule level110 were reported. In contrast to the use of Fe(III) in a catechol system, the collaboration team of Lee and Lee found that the gelation kinetics of catechol‐conjugated polymers dramatically differs when using vanadium ions.…”
Section: Studies By Kaist Faculty Membersmentioning
confidence: 99%
“…An example of this approach is the work done by Gref et al who studied the use of a MOF obtained by reacting Fe(III) and trimesic acid as an anti-HIV AZT-TP drug delivery system [63]. Other examples are the work of Keskin and Kızılel about the antiviral drug delivery uses of three different MOFs developed by reacting Zn 4 O(CO) 2 and three different dicarboxylate linkers [64] and the work Novio et al about the uses of iron-catechol-based MOFs as antiviral drugs delivery systems [65].…”
Section: Supporting Rolementioning
confidence: 99%